Physico-Morphological Characteristics and Oxidative Markers of Fresh Semen of Gir Bulls - Prajapati, Sunnykumar G.; Vala, Karsan B.; Singh, Vivek Kumar; Solanki, Gajendra B.; Chavda, Bhakti P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present investigation was undertaken on four mature Gir bulls (4-6 years) maintained at University farm, Junagadh for 4 months during hot summer season. Semen (n=6 ejaculate/bull) was collected using artificial vagina once a week from each bull. The fresh ejaculates were evaluated for physical attributes and oxidative stress markers in the seminal plasma. The overall mean values recorded based on 24 ejaculates for ejaculate volume, sperm concentration, mass motility (0-5 scale), individual motility, sperm viability, sperm abnormality, plasma membrane integrity (HOST reactive sperm), and acrosome integrity were 6.20 ± 1.27 mL, 1316.83 ± 155.07 million/ mL, 3.75 ± 0.20, 84.83 ± 0.94 %, 87.58 ± 1.07 %, 9.63 ± 0.83 %, 79.58 ± 1.01 % and 91.21 ± 0.52 %, respectively. There was a significant P<0.001) difference in ejaculate volume, sperm concentration and sperm abnormality between bulls. The levels of oxidative stress parameters, viz. lipid peroxidation and glutathione S-transferase (GST) activity in the seminal plasma were 5.51 ± 0.26 μmol/mL and 16.30 ± 2.14 nmol/ mL/min, respectively. Individual motility, viability, HOST reactive spermatozoa, and acrosomal integrity were positively correlated, suggesting that any one or two attributeslike motility or HOS test can predict the semen quality. The semen quality generally was in normal physiological range including oxidative markers even during heat stress.